Linguistic Landscape of Multilingual Informative Signage at Jawa Timur Park 2, Indonesia - Noviana, Ananda Putri; Indah, Rohmani Nur (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
Lack of visibility of information in tourist areas threatens the credibility and image of Indonesian tourism at the global level. In the context of globalization that encourages multilingualism practices, the choice and use of languages on signs becomes a crucial aspect. Therefore, this study highlights how tourist destinations in Indonesia, especially Jawa Timur Park 2, navigate these challenges. This study aims to explore the language displayed on informative signage in the educational tourism destination and visitors’ reactions to it. It looks at the linguistic landscape phenomenon from three perspectives, namely Spolsky and Cooper’s (1991) taxonomy of signs, Sebba’s (2013) language writing, and Garvin and Mathiot’s (1968) positive language attitudes. The method used is descriptive qualitative, with the first primary data in the form of phrases, sentences, and paragraphs in informative signage, and the second primary data in the form of visitor statements from questionnaire responses. The findings reveal the existence of multilingual, bilingual, and monolingual sign types to convey detailed information, object names, and place names. In addition, the languages used are Indonesian, English, and scientific language from Greek/Latin. Visually, the language is written in symmetrical, asymmetrical, and mixed language-spatial relationships. The language is written in equivalent, disjoint, and overlapping language-content relationships. The visitors’ positive attitudes towards national and international languages are addressed by language loyalty and pride. Thus, this study suggests that tourism officers, sign designers, and tourism policy makers consider language use on monolingual, bilingual, and multilingual signs that are adequate, inclusive, and functional for all visitors.